The authority of narration in the Arab folklore tradition as Kalila wa Dimna in representation (Journal of the College of Basic Education, 2023)
Does narration (1) - how can it be - have authority? Does the narrator - as does the poet - have an advantage that distinguishes him fromabout others? Why was the traditional narration associated with the fate of the narrator, with his existence? Let's seeAl-Harith influenced by Persian stories, and influential in the Quraish community during the Islamic callThe Messenger of God, may God’s prayers and peace be upon him, sheds his blood, then he is killed after the Battle of Badr (2).A story: ((There is salvation in it)) (3) as she put it. And Abu al-Fath al-Iskandari is researchingHis existence - materially and socially - through deceit and deceit, and he justifies this by saying in the metaphorsimian: